TATA RUANG DAN ELEMEN ARSITEKTUR PADA RUMAH JAWA DI YOGYAKARTA SEBAGAI WUJUD KATEGORI POLA AKTIVITAS DALAM RUMAH TANGGA - Cahyandari, Gerarda Orbita Ida (Universitas Atma Jaya Yogyakarta, 2012)
Abstract: Traditional houses resemble classification according to social status of the owner. Traditional house is a manifestation of symbolic and cultural meaning. Javanese traditional houses are represented in certain orders and characteristics. â€œNdalemâ€ in the form of â€œJogloâ€ is a type of high status. â€œLimasanâ€ and â€œKampungâ€ are houses for medium and low status. Activities in a house reflect social inter-relationship in a family. Javanese people are categorized as patrileneal family systems that have cultural determination in domestic roles. The analysis requires historical data, pattern of activity, and architectural elements and symbols. Mapping of activities draws housing classification. â€œDalemsâ€ and â€œjoglosâ€ have spaces to support social activity and define the roles. Houses in lower classification show balance of the roles.Keywords: social classification, Javanese traditional house, domestic rolesAbstrak: Rumah tradisional mencitrakan status sosial pemilik yang juga berarti bahwa rumah tradisional memiliki makna simbolis dan kultural. Rumah trdisional Jawa diwujudkan dalam aturan dan karakteristik tertentu. Rumah â€œJogloâ€ dalam bentuk â€œNdalemâ€ berada pada status sosial pemilik yang tinggi, sedangkan Limasan dan Kampung dimiliki oleh kaum biasa dan rakyat jelata. Aktivitas dalam rumah mencerminkan hubungan social dalam suatu rumah tangga. Keluarga jawa termasuk penganut system patrilineal yang berpengaruh pada peran domestik. Analisis menggunakan data historis, pola aktivitas, dan elemen serta simbol arsitektural. Pemetaan aktivitas menunjukkan klasifikasi bangunan. Ndalem dan joglo memiliki ruang yang mendukung aktivitas dan peran sosial. Rumah dalam klasifikasi yang lebih rendah, menunjukkan peran domestik dan sosial yang seimbang.Kata kunci: klasifikasi sosial, rumah tradisional Jawa, aktivitas rumah tangga